Habituasi Gerakan Maghrib Mengaji Pada Masyarakat Desa Pakkabba Kabupaten Takalar - Rahman, Abdul (Solidaritas: Jurnal Pengabdian, 2022)
The Mahgrib Mengaji program was launched by the Ministry of Religion of the Republic of Indonesia on April 14, 2013. The program gets attention and good response from local governments in various regions of the Republic of Indonesia and continues today, including in the Takalar District. Along with the rate of development of technology, information, and communication, the community began to leave the Maghrib Mengaji program, including in Pakkabba Village, because the younger generation of the community put more engagement to social media and television shows. This community service activity aims to provide a deep understanding of the implementation of the Maghrib Mengaji program and create awareness of reading and practicing the contents of the Quran. The community service team provides socialization and assistance to the Pakkabba Village community to habituate the Maghrib Mengaji program. Service activities are carried out by socializing the importance of reading the Quran and assisting Maghrib Mengaji habituation activities carried out from the house to house. Community service activities are carried out with socialization and assistance with the following stages: planning, implementation, monitoring, and administration. The activity results show that the people of Pakkabba Village have high enthusiasm for implementing the Maghrib Mengaji Program and getting support from the government and community leaders. Service activities received approval and support from the community, including the government and local community leaders.